The practice of self medication by university students (Research, Society and Development, 2021)
This work aims to highlight and discuss the data described in the literature about self-medication among university students, as well as to analyze the factors that contribute to this practice. In this study, a data collection was carried out in PubMed®, Google Acadêmico®, Latin American Literature in Health Sciences and Science Direct, based on the descriptors: self-medication and students. After refining the search and applying the inclusion criteria, 23 articles that referred to the theme of this study were compiled in this review. It was observed that 51.7% of students in health courses use drugs without a prescription, even though they have full knowledge of the risks that this practice can bring to health, the prevalence of self-medication among university students ranged from 36.1% to 99.5%. Among the main classes of drugs used, anti-inflammatory drugs stood out 23,3% and analgesics 31,4%. The factors that are linked to the self-medication practice among university students are the accessibility to purchase medications without medical prescription, the delay in the attendance of the public health system, the high values ​​of private consultations and the great availability of information available on the internet. This self-medication behavior can trigger chronic pain incidences. Since the use of a specific medication on a frequent basis, can make its effect is no longer perceived, causing the individual to ingest higher doses. Therefore, it is concluded that it is necessary to implement educational methods in universities, especially among academics in health courses. Using strategies that make them aware and create an approach on the rational use of medicines in transversal disciplines throughout the graduation.